Analysis of a current state of energy and ecological sector of Kazakhstan (Eurasian Journal of Ecology, 2019)
The analysis of a current state of energy and ecological sector of Kazakhstan which is carried out according to basic provisions «The global energy and ecological strategy of a sustainable development in the XXI century» presented in the book of the President of the Republic of KazakhstanN. A. Nazarbayev is provided inthis paper. The energy sector represents theleading unit of social and economic life of Kazakhstan, a basis of its fuel andenergy complex (FEC). On a condition of energy industry the territory of thecountry can be divided conditionally into 3 zones: northern, western andsouthern. The balance of power of the electric energy on zones is given. Theshare of various types of power plants and a ratio of the used resources forgeneration of an electric energy in Kazakhstan is shown. Power plants areclassified by national, industrial and regional value. The main features ofstructure of a power complex of Kazakhstan, prospects of using alternativeresources of energy are marked out. Preservation of technological balance«traditional power – renewable» consists in strategic planning of system ofnational and international energy and ecological safety.Key words: fuel and energy complex, power plants, energy, ecology,energy and ecological strategy, alternative resources of energy, устойчивое развитие, Kazakhstan.